Fact vs. Speculation: Finding the Meaning Behind the Westmoreland Slaughterhouse, Pottawatomie County, Kansas, 1859 – 1959 - Zuk, Lara (Kansas State University. Dept. of History, 2011)
With Germanic and possibly surviving medieval European culture ways implanted in Pottawatomie County, a shared rural slaughterhouse in early Westmoreland provides clues. From oral accounts only, the author locates the site of the original slaughterhouse and discusses its use as a shared resource by early German farmers in the area. This study contains interviews and photographs.
Keywords: Pottawatomie County; Westmoreland; Slaughterhouse; German culture; Butchering